The Influence of Halal Production and Sharia Banking Financing on Halal Food and Beverage Exports in Indonesia in 2018 - 2022 - Meilin, Rinelisa; Sri Muljaningsih (Islamic Economics and finance in Focus, 2026)
This study aims to analyze the influence of halal production on exports of the halal food and beverage industry in Indonesia and the influence of Islamic banking financing on exports of the halal food and beverage industry in Indonesia. This study uses a quantitative approach with a regression study. The results of this study indicate that halal production, proxied by the total production of halal-certified food and beverages, has a significant and positive effect on exports of the halal food and beverage industry in Indonesia. This indicates that increasing domestic halal production volume will significantly increase exports. This condition is in line with the view that product quality assurance and halal certification are important factors in boosting the competitiveness of Indonesian halal products in the global market. Islamic banking financing, proxied by total financing of the processing industry sector, does not significantly affect exports of the halal food and beverage industry. This result is thought to be due to the still low proportion of productive financing channeled to the real sector, particularly the halal food and beverage industry. Data show that the structure of Islamic financing during the study period was still dominated by consumptive financing, thus not being able to optimally drive export performance